The relationship between work stress, life satisfaction and burnout in employees in Jakarta - Prayoga, I Made Andika; Hendryadi, Hendryadi (Indonesian Journal of Business, Accounting and Management, 2024)
This study aims to analyze the relationship between work stress, life satisfaction, and burnout among employees in Jakarta. The research method employs a quantitative approach, collecting data through questionnaires distributed to 119 employee respondents in the Jakarta area. The research instruments used have been tested for validity and reliability. The data analysis techniques applied were Confirmatory Factor Analysis (CFA) and regression testing using Jamovi to validate the relationship model between variables. The results of the study show that: (1) Work stress has a positive and significant effect on burnout; (2) Burnout has a negative and significant effect on life satisfaction; (3) Work stress has a positive and significant effect on life satisfaction, but this effect becomes negative when mediated by burnout. These findings reveal the critical role of burnout as a mediator variable that reverses the direction of the relationship between work stress and life satisfaction. Article Information:Received 10/31/2024 / Revised 11/6/2024 / Accepted 11/27/2024 / Online First 12/20/2024